Effect of Fiber Reinforcement Flexible Pipeline on Hydrogen Transportation—A Review - Ahmed Elkelity; Yu Cao; Mahmoud El-Wazery; Yong Bai; Fang Wang (Results in Engineering)
The reinforcement of flexible pipelines with fiber for hydrogen transportation is an essential field of research due to its importance in industries. Recent developments by companies in manufacturing fiber-reinforced flexible pipes highlight weight reduction and improved strength. It explains the development of research methodologies for flexible pipelines in hydrogen transportation, including experimental, analytical, and numerical simulation methods. The research focuses on the mechanical and structural advantages of fiber-reinforced polymer composites (FRPC) in hydrogen transportation and its challenges, particularly in marine applications (offshore/subsea) where exhibit 30–50% lower lifetime costs attributed to less maintenance and longer service life. The study highlights the economic feasibility and design consideration necessary for scaling hydrogen transportation networks, emphasizing the importance of materials selection and mechanical testing for best performance and using various simulation software. In summary, a comparison between traditional steel pipelines and fiber-reinforced composites highlights the latter's benefits, including weight reduction of 40–60%, reduce pipeline mass by up to 77.7%, with an 85.06% increase in tensile stiffness, corrosion resistance, and better fatigue performance. Flexible steel pipes might be replaced by hybrid composites with fiber reinforcement, such as glass and carbon, depending on transportation requirements for cost-effectiveness which offer 15–25% over steel pipelines and efficiency in the hydrogen area. Analytical methods enhance predictive capabilities, material quality, design verification, risk mitigation, and innovation in composite pipeline construction.